PENGENALAN KENDARAAN KLASIK DENGAN MEMANFAATKAN MOBILE AUGMENTED REALITY - Ivo Andriano; Suendri Suendri; Ali Ikhwan (UIN Sumatera Utara Medan, 2022)
Augmented Reality is a combination of a virtual world (virtual) and a real world (real) created by computers. Virtual objects can be in the form of tests, animations, 3D models or videos that combine with the actual environment so that the user feels the virtual object is in their environment. In Augmented Reality technology, classic vehicle recognition media is an application that uses the markerless method, where in this method later using a marker as a pointer or marker to bring up 3D objects. This application helps users make it easier to find out about classic vehicles in the city of Medan, without having to search the internet and even on other social media. In its use, this application runs on the Android operating system so that it can make it easier for users to access the application.